Strategi Desain Konsep Permakultur pada SMK Pertanian di Kabupaten Grobogan - Rizkia Rahmani Maulana; Suparno Suparno; Ana Hardiana (ARSITEKTURA, 2019)
Grobogan Regency is one of the regions that has high agricultural potential. However, the existing educational facilities cannot accommodate all existing communities. Education in agriculture is found as lacking where not all regions who potentially in agriculture have agriculture-based educational institutions. Agricultural Vocational High School with the concept of permaculture in Grobogan provides five departments in agriculture with a three-year study period. Planning method in this design using planning, programming and designing which related to permaculture concept. Permaculture is the basis for ecological and independent building design by emphasizing the main principles of permaculture; energy planning, energy cycle, scale, biological sources and related locations that are in accordance with the needs of the education and agriculture regions. Design of agricultural vocational school emphasizes on zoning in building and sector. The result of the school design is to create an independent school area with maximum energy planning and to display related agricultural school buildings.